Obesity Alters Endoxifen Plasma Levels in Young Breast Cancer Patients: A Pharmacometric Simulation Approach. Issue 3 (23rd July 2020) - Mueller‐Schoell, Anna; Klopp‐Schulze, Lena; Schroth, Werner; Mürdter, Thomas; Michelet, Robin; Brauch, Hiltrud; Huisinga, Wilhelm; Joerger, Markus; Neven, Patrick; Koolen, Stijn L.W.; Mathijssen, Ron H.J.; Copson, Ellen; et al.
Abstract : Endoxifen is one of the most important metabolites of the prodrug tamoxifen. High interindividual variability in endoxifen steady‐state concentrations (CSS, min ENDX ) is observed under tamoxifen standard dosing and patients with breast cancer who do not reach endoxifen concentrations above a proposed therapeutic threshold of 5.97 ng/mL may be at a 26% higher recurrence risk compared with patients with endoxifen concentrations exceeding this value. In this investigation, 10 clinical tamoxifen studies were pooled (1, 388 patients) to investigate influential factors on CSS, min ENDX using nonlinear mixed‐effects modeling. Age and body weight were found to significantly impact CSS, min ENDX in addition to CYP2D6 phenotype. Compared with postmenopausal patients, premenopausal patients had a 30% higher risk for subtarget CSS, min ENDX at tamoxifen 20 mg per day. In treatment simulations for distinct patient subpopulations, young overweight patients had a 3.1–13.8‐fold higher risk for subtarget CSS, min ENDX compared with elderly low‐weight patients. Considering ever‐rising obesity rates and the clinical importance of tamoxifen for premenopausal patients, this subpopulation may benefit most from individualized tamoxifen dosing.